STUDI PERENCANAAN SISTEM DRAINASE KAWASAN PERUMAHAN PEMUKIMAN DESA SUNGAI MERIAM - ZAGLADI, MUHAMMAD REZA (KURVA S JURNAL MAHASISWA, 2017)
The need for good road infrastructure is a good thing that is expected by the community and is a supporting factor for the smoothness of the economy and the opening of isolated areas. In the planning process it is necessary to consider the factors such as comfort, safety, environment and other factors that support planning and mature planning..Planning of drainage of residential area of Meriam River Village Anggana Samarinda Sub District covers construction engineering planning and the causes of flood / puddle, basically can be divided into two, that is due to local natural conditions such as relatively high rainfall, topographic conditions are sloping, and the influence the back water from the river or the sea. Tujuan dari penelitian ini adalah mendapatkan besar debit banjir pada saluran drainase lingkungan perumahan pemukiman Desa Sungai Meriam Kecamatan Anggana Samarinda serta dimensi saluran yang dapat menampung hingga tahun 2041.In this study for primary data obtained from the actual data retrieval in a certain period with the intention of Conducting calculations in order to accommodate the flood discharge for the re-time 2, 5, 10, 15, 25 and Conduct channel dimensions.